Marketing Problems and Opportunities in Nepal - Bhatta, Mukesh Prasad (KVM Research Journal, 2025)
Marketing plays a pivotal role in the growth and sustainability of businesses, yet companies in Nepal face a variety of challenges that hinder effective market performance. This study explores the marketing problems encountered by businesses in Nepal, including limited market research, inadequate infrastructure, high competition, and evolving consumer behavior. It also examines potential opportunities such as the growing digital marketplace, increasing consumer awareness, and emerging niche markets. Using a combination of primary data from surveys and interviews with business owners and secondary data from reports and studies, the research identifies key factors affecting marketing effectiveness. The findings highlight the need for innovative strategies, adoption of digital marketing tools, and consumer-centric approaches to overcome challenges and capitalize on opportunities, ultimately contributing to business growth and sustainable market development in Nepal.